Monitoring ozone in different spectral regimes from space and balloon (Sentinel-4/-5P, TELIS) - Jian Xu; Schreier, Franz; Loyola, Diego; Schussler, Olena; Doicu, Adrian; Trautmann, Thomas (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2016)
Recently, several new generation instruments for remote sensing of the Earth's atmosphere from space and balloon have been launched and planned. The German Aerospace Center (DLR) has engaged in research activities for a number of missions, e.g. GOME/GOME-2 (Global Ozone Monitoring Experiment), Sentinel-4/-5P, and TELIS (TErahertz and submillimeter LImb Sounder). Inverse problems occurring in atmospheric science aim to estimate atmospheric state parameters from these remote sensing data. On the subject of these ill-posed inverse problems, the major challenge concerns the choice of the inversion algorithm balancing up accuracy and efficiency. The objective of this study is to look into the effectiveness of the regularized nonlinear iteration scheme and the neural network-based scheme. Practical implementations pertaining to ozone profiling from spaceborne and balloon-borne measurements are addressed.